PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA MATA PELAJARAN BIOLOGI KELAS XI MIA 2 SMAN 1 PEKANBARU TAHUN AJARAN 2018/2019 - Lius, Indah Rahmawati; Natalina, Mariani; Yustina, Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to improve scientific literacy of student class XI MIA 2 SMAN 1 Pekanbaru by implementation guided inquiry model. It had been done in SMAN 1 Pekanbaru on March of May 2019. Parameters measure were student’s scientific literacy competencies, scientific literacy knowledge, student’s achievement, and scientific literacy attitudes. The type of this research was classroom action research by implementation guided inquiry model. It had been done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The research instrument used was a learning device that consist of a lesson plan, syllabus, assesment authentic sheet, observation sheet and scientific literacy competencies skill sheet. The collected data was analysed descriptively. The result of this research showed that scientific literacy competencies on first cycle was 81,89 (C) and increased on second cycle up to 86,80 (B). The result of this research showed that scientific literacy knowledges on first cycle was 79,97 (C) and increased on second cycle up to 88,01 (B). Student’achievement on first cycle was 80,09 (B) and increased on second cycle up to 85,46 (B). Classical completeness percentage on first cycle was 88,89% and increased on second cycle up to 100%. Student’s scientific literacy attitudes on first cycle was 80,77 (C) and increased on second cycle up to 89,18 (B). It can be conclude that guided inquiry model can improve scientific literacy of student class XI MIA 2 SMAN 1 Pekanbaru.Key Words: Guided Inquiry, Scientific Literacy, Biology Lesson